Implikasi Indikator Trustworthy News AMSI Tingkat Mikro Ditinjau dari Perspektif Teori Dependensi - Hasrullah, Hasrullah; Rahmadani, Noviyanti Putri (Calathu: Jurnal Ilmu Komunikasi, 2024)
This research discusses the 11 media trustworthiness indicators initiated by the Indonesian Cyber Media Association (AMSI), their correlation with micro-level media dependency based on the media dependency theory by Sandra Ball-Rokeach and Melvin DeFleur. The dynamics of the current media-audience relationship have prompted researcher to examine how discourse on these indicators impacts media dependency amid a plethora of information sources and uncertainties. However, this research is limited to micro levels of dependency. Previous studies have depicted media dependency in society as per its applications. Yet, viewing trustworthy media indicators as a crucial factor in media dependency and its effects remains limited. Therefore, the aim of this study is to explore and theoretically define the implications of these trustworthy news indicators. This is a qualitative study using a library research design and textual analysis of secondary data. The results, trustworthy news indicators have the potential to significantly influence current media dependency. The media dependency factors in the media-individual relationship shows that news trust indicators enhance the media's ability to be a reliable information source and meet audience needs. These indicators impact media dependency effects, such as the cognitive aspect to strengthen the audience's ability to critically evaluate information, the affective aspect to foster positive emotions, and the behavioral aspect to guide audience behavior in news consumption. This research can offer recommendations for media in future decision-making, provide a public framework for determining positive media dependency, and serve as a theoretical foundation for further research related to trustworthy news indicators. Keywords: implications, trustworthy news, micro, media dependencies, audience